Human adult T-cell leukemia virus: molecular cloning of the provirus DNA and the unique terminal structure. - Seiki, M (1982)
Adult T-cell leukemia virus (ATLV) is a human retrovirus closely associated with adult T-cell leukemia. The integrated provirus DNA and cDNA from virion RNA were molecularly cloned and their structures were analyzed. Clone lambda ATM-1 of an integrated provirus DNA in the MT-1 cell line, established from adult T-cell leukemia cells by cocultivation with cord lymphocytes, contained DNA about 13,000 base pairs (bp) long and long terminal repeats (LTR) at both ends of the viral sequence that were about 8,000 bp long. These two LTR sequences were linked to cellular sequences with direct repeats of 7 bp. Each LTR consisted of 754 bp including inverted repeats of 2 bp at the ends and the T-A-T-A-A box, characteristics in common with those of LTRs of other known retroviruses. Adjacent to the 5' LTR there was a sequence identical to the tRNAPro binding site in murine leukemia virus, suggesting that tRNAPro is a primer for reverse transcription of the viral genome. From these structural features, the mechanism of ATLV replication was suggested to be the same as that of other known animal retroviruses. However, the length of the small terminal repeats at the ends of the RNA genome, 228 +/- 1 bases, is much longer than the lengths, up to 80 bases, of those in avian, mouse, or primate retroviruses so far analyzed. These findings suggest that ATLV should be classified in a distinct group of retroviruses with bovine leukemia virus which also makes unusually long strong-stop cDNA.